Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1292/jvms.64.873
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bovine Lactoferrin by the Intramammary Infusion in Cows with Staphylococcal Mastitis during the Early Non-Lactating Period.

Abstract: ABSTRACT. To evaluate the clinical effects of bovine lactoferrin on staphylococcal mastitis in Holstein cows during the early non-lactating period, 41 mammary quarters were selected randomly from 36 cows on 3 dairy farms. Twelve quarters were infused intramammarily with bovine lactoferrin. Twenty-nine quarters were infused with antibiotic as a control. In the bovine lactoferrin-infused group, 91.7% of mastitic quarters were cured at 7 days after calving, compared with 48.3% in the control group. Furthermore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…In all studies, great individual variations in bLf concentration between cows have been reported. Exogenous Lf has been proposed to represent a potential nonantibiotic therapeutic approach for the treatment of IMI (11,24). Some beneficial effect was reported for subclinical mastitis (26), but for experimental E. coli mastitis, no clear advantage could be demonstrated (33).…”
mentioning
confidence: 99%
“…In all studies, great individual variations in bLf concentration between cows have been reported. Exogenous Lf has been proposed to represent a potential nonantibiotic therapeutic approach for the treatment of IMI (11,24). Some beneficial effect was reported for subclinical mastitis (26), but for experimental E. coli mastitis, no clear advantage could be demonstrated (33).…”
mentioning
confidence: 99%
“…The Lf injected cows (n=10) were intra-mammarily injected in the mastitic quarters with 200 mg of Lf per quarter in 10 ml of sterile phosphate buffered saline (PBS) pH7.2 through the teat canal [16]. In the cows with combination therapy of both Lf and antibiotics (n=9), Lf was injected into the mastitic MG at 3 days after antibiotics injection (0 days post injection (dpi)).…”
Section: Injection Of Lf Into Mammary Glands (Mgs)mentioning
confidence: 99%
“…MGSs were measured for each SCC, S.aureus counts, the concentration of Lf, content rate of Con A low-affinity Lf and the mRNA expression of tumor necrosis factor α (TNFα) in MG cells. The causative staphylococci in mastitic MGSs were isolated with staphylococcus No.110 agar medium (Nissui Pharmaceutical Co., Ltd., Tokyo, Japan), and the S.aureus counts were measured as described by Kai et al [16,17]. The coagulase production was determined by tube test of rabbit plasma (Eiken Chemical Co., Ltd., Tokyo, Japan).…”
Section: Injection Of Lf Into Mammary Glands (Mgs)mentioning
confidence: 99%
See 2 more Smart Citations